INA MOVEMENT IN MANIPUR AND PEOPLE’S PARTICIPATION - Luwangningthou, Maisnam; Singh, Soibam Athoiba (International Journal of Research -GRANTHAALAYAH, 2026)
The Indian National Army (INA) movement constitutes an important chapter in the history of India’s freedom struggle, particularly in the eastern frontier region of Manipur during the Second World War. This article examines the historical context of the rise of nationalism in Manipur, the advance of the INA into the region, and the nature of popular participation in the movement. It argues that long-term political mobilisation since the 1930s, women-led anti-colonial protests, and growing dissatisfaction with British colonial policies created a receptive environment for the INA. The study highlights the role of prominent Manipuri figures such as Mairembam Koireng Singh and Hemam Nilamani and analyses the participation of ordinary men and women who supported the movement through logistics, intelligence, and voluntary enlistment. Although the INA campaign in Manipur failed to achieve its immediate military objectives, it had a profound political and psychological impact, intensifying nationalist consciousness and integrating Manipur more firmly into the broader narrative of India’s struggle for independence.